Applications of Soft Systems Methodology for Organizational Change - Ebrahimi, Maryam, 1980- (US: IGI Global, 2020)
"This book provides a theoretical foundation and practical practice of soft systems methodology in organizations"--
Includes bibliographical references (pages 229-232) and index.
Keywords: Organizational change; System theory